2020
DOI: 10.17221/50/2020-pse
|View full text |Cite
|
Sign up to set email alerts
|

Garden pansy (Viola × wittrockiana Gams.) - a good candidate for the revitalisation of polluted areas

Abstract: In the current studies, heavy metal tolerance level, accumulation efficiency and sexual reproduction were determined in Viola × wittrockiana, a non-metallophytic ornamental cultivar in comparison to V. tricolor, a metallophyte, after zinc (Zn) or lead (Pb) treatment (0, 10, 100 and 1 000 ppm) in pot experiments. The seed germination frequency that was not reduced in comparison to the control, the effective Zn absorption from the soil and exclusion strategy for Pb, as well as the regular sexual reproduction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…High tolerance of the cells of Viola · wittrockiana , a common bedding plant, is not an unexpected result. Sychta et al, 2020 [ 9 ] based on pot experiments measuring seed germination, heavy metal accumulation and sexual reproduction under the Zn and Pb treatments, confirmed that this non-metallicolous ornamental species could be treated as another metal-tolerant violet of similar tolerance to the metallicolous genotype of V. tricolor . Comparing our results with two accumulators Jatropha curcas and Prosopis laevigata [ 46 , 47 ], whose response to heavy metals varied depending on the metal applied, the dose and duration, is unauthorized neither due to the different methodology (biomass weight vs. cell viability) nor due to the fact that, in the latter biomass of all, not only living cells were measured.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…High tolerance of the cells of Viola · wittrockiana , a common bedding plant, is not an unexpected result. Sychta et al, 2020 [ 9 ] based on pot experiments measuring seed germination, heavy metal accumulation and sexual reproduction under the Zn and Pb treatments, confirmed that this non-metallicolous ornamental species could be treated as another metal-tolerant violet of similar tolerance to the metallicolous genotype of V. tricolor . Comparing our results with two accumulators Jatropha curcas and Prosopis laevigata [ 46 , 47 ], whose response to heavy metals varied depending on the metal applied, the dose and duration, is unauthorized neither due to the different methodology (biomass weight vs. cell viability) nor due to the fact that, in the latter biomass of all, not only living cells were measured.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lower mobility and limited use (for plants) of lead compared to zinc, cells treated with the same amount of either Zn or Pb accumulated at least several times more Pb than Zn. Although this trend is not observed in the field, where violets accumulate more zinc than lead in roots and in the aboveground parts [ 25 ], high BF (above 4) was confirmed in V. tricolor treated (to the soil) with 10 and 100 ppm of Pb [ 9 ]. Similarly, high BF was also observed in V .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations